HUBUNGAN ASUPAN ASI EKSLUSIF DENGAN KUALITAS BERAT BADAN PADA ANAK USIA 0-6 BULAN DI DESA RANCABANGO PATOKBEUSI: THE RELATIONSHIP OF EXCLUSIVE BREASTFEEDING WITH THE QUALITY OF BODY WEIGHT IN CHILDREN AGED 0-6 MONTHS IN RANCABANGO PATOKBEUSI VILLAGE - Tika Sri Mulyani; Puji Raharja Santosa; Lisna Agustina; Fauziah Fauziah; Rahmawati Rahmawati (Borneo Nursing Journal (BNJ), 2023)
Breast milk is the first natural food for babies that provides all the vitamins, minerals, and all the nutrients needed by babies for growth in the first six months and no other food or fluids are needed. Breast milk fulfills half or more of a child's nutritional needs in the first to second year of life (WHO, 2002). Body weight is one of the anthropometric indicators to assess growth in infants or children. There are several ways that can be done to increase the baby's weight by providing good nutrition. Research objective:to determine the relationship between. exclusive breastfeeding intake and the quality of body weight in children aged 0-6 months in the village of Rancabango Patokbeusi Subang Research method:This research method is correlative analytic using a cross sectional study approach. The population of this study is infants aged 0-6 months with exclusive breastfeeding at the UPTD Public Health Center of Rancabango Patokbeusi Subang. By using purposive sampling technique. Research Results:based on the results of statistical analysis using the Chi Square test obtained a P_Value of 0.001<0.05. This shows that Ha is accepted. Conclusion: there is a relationship between exclusive breastfeeding intake and the quality of body weight in children aged 0-6 months in the village of Rancabango Patokbeusi Subang.